Analysis of Student Errors in Solving Matrix Problems in Class XI of SMK Muhammadiyah Delanggu - Salsabila, Safira; Utami, Nida Sri (Universitas Sembilanbelas November Kolaka, 2023)
This study sought to describe mistakes made by SMK Muhammadiyah Delanggu's grade XI students with high, medium, and low abilities when solving matrix problems. It also sought to describe mistakes made by SMK Muhammadiyah Delanggu's grade XI students with concepts, principles, and procedures. This exploration is an engaging subjective examination. The instrument utilized a composed test that included two things, four framework material test questions and meetings were utilized as extra instruments. 14 XI students who had studied matrix material served as the study's subjects. By gathering information from giving composed test questions, understudy mistakes can be distinguished. According to the findings of this study, students of high ability understood the concepts and principles, but performed mathematical operations incorrectly; students of medium ability made procedural errors due to a lack of accuracy in matrix multiplication calculations; and students of low ability made numerous concept, principle, and procedure errors.